Essentials of modern business statistics with Microsoft Excel - Williams, Thomas A. (Thomson/South-Western, 2004)
This edition provides an introduction to business statistics that balances a conceptual understanding of statistics with the real-world application of statistical methodology. Microsoft Excel is integrated throughout the text, showing step-by-step instructions and screen captures to aid learning